2021
DOI: 10.3390/su13052429
|View full text |Cite
|
Sign up to set email alerts
|

Water-to-Cement Ratio of Magnesium Oxychloride Cement Foam Concrete with Caustic Dolomite Powder

Abstract: Magnesium oxychloride cement (MOC) foam concrete (MOCFC) is an air-hardening cementing material formed by mixing magnesium chloride solution (MgCl2) and light-burned magnesia (i.e., active MgO). In application, adding caustic dolomite powder into light-burned magnesite powder can reduce the MOCFC production cost. The brine content of MOC changes with the incorporation of caustic dolomite powder. This study investigated the relationship between the mass percent concentration and the Baumé degree of a magnesium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In other words, the lower the water content, the higher the bonding shear strength of the MOC binder. This was because the excess H 2 O reacted more with MgO, resulting in a higher content of Mg(OH) 2 , which reduced the strength of the binder [ 25 ]. Excess water could also have caused pores and contributed to the observed reduction in strength [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, the lower the water content, the higher the bonding shear strength of the MOC binder. This was because the excess H 2 O reacted more with MgO, resulting in a higher content of Mg(OH) 2 , which reduced the strength of the binder [ 25 ]. Excess water could also have caused pores and contributed to the observed reduction in strength [ 23 ].…”
Section: Resultsmentioning
confidence: 99%
“…The curing of MOC at different temperatures between 0 °C and 65 °C was also investigated. It was shown that the curing at temperatures between 20 °C and 50 °C resulted in the most stable MOC under humid conditions [ 25 ]. When curing occurs at a higher temperature, a certain amount of unreacted MgO remains in the system [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…The brine content of MOC changes with the incorporation of caustic dolomite powder. The study of Zheng et al [39] in this special issue investigated the relationship between the mass percent concentration and the Baumé degree of a magnesium chloride solution after bischofite (MgCl 2 •6H 2 O) from a salt lake was dissolved in water. Then the proportional relationship between the amount of water in brine and bischofite and the functional formula for the water-to-cement ratio (W/C) of MOC mixed with caustic dolomite powder were deduced.…”
Section: Overview Of This Special Issuementioning
confidence: 99%
“…Ordinary Portland cement, quick-hardening Portland cement, sulfate-resistant Portland cement, and high alumina cement can be used as a binder in foam concrete and as additional materials to replace part of the cement in the range from 10% to 70% in place of materials such as microsilica, fly ash, lime, ground granulated blast-furnace slag, and others. As a rule, various additional components in addition to the main raw material are used to improve the mechanical and physical characteristics [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ]. Table 2 provides an overview of various ways to modify and improve the physical–mechanical characteristics by introducing additional components.…”
Section: Introductionmentioning
confidence: 99%